Relationships Between Sleep Problems and Stress Coping Strategies Adopted by Nurses Including Socio-Occupational Factors - Kowalczuk, Krystyna; Krajewska-Kułak, Elżbieta; Sobolewski, Marek (Frontiers in Psychiatry, 2021)
Introduction: The health of nurses has a direct impact on the quality of care and health outcomes for patients. The length and quality of sleep as well as the intensity of perceived stress have an impact on the health of nurses. An appropriate stress coping strategy can reduce the impact of stress and mitigate its negative consequences. Aim: The purpose of this study was to investigate relationships between excessive sleepiness and insomnia in interaction with selected socio-occupational factors and stress coping strategies among nurses. Material and method: The cross-sectional study was conducted among 448 nurses working in hospitals in Podlasie Province in Poland. Mini-Cope inventory - the polish adaptation of Carver’s BriefCope was used for measuring coping with stress. Sleep problems were assessed using the Athens Insomnia Scale and the Epworth Sleepiness Scale. Results: The most frequent used coping strategies were active strategies (active coping, planning). The least-used were avoidant strategies (behavioral disengagement, substance use). Excessive sleepiness affected 38% of surveyed, while insomnia 33%. Excessive sleepiness was most strongly related with behavioural disengagement (R2=18.6%), substance use (R2=17.5%), humour (R2=13.8%) and denial (R2=12.0%) while insomnia with substance use (R2=17.5%) and self-blame (R2=15.9%). Nurses with tertiary education experiencing sleep problems less frequently used the strategy of humour, behavioural disengagement, substance use and religion than with lower education. Nurses working in interventional wards experiencing excessive sleepiness used the strategy of humour, religion and positive reframing less often than those working in other wards while those suffering from insomnia used the strategy of humour more often than those working in other wards. Conclusions: The implementation of avoidant and support-seeking and emotion-oriented stress coping strategies by nurses were associated with the sleep problems. Tertiary education discourages nurses with sleep problems from using avoidant coping strategies and devoting themselves to religion. Education and improvement of the quality of sleep may prevent nurses from resorting to stress coping strategies that have a detrimental effect on their health and well-being.